Microbial Battlefront: Exploring the In-vitro Inhibitory Effects of Homeopathic Medicines on Streptococcus mutans (International Journal of Food and Nutritional Sciences, 2022)
Background: Dental caries is known to be one of the commonest bacterial infectious disease in humans1. Streptococcus Mutans is the leading cause of dental caries worldwide. An ecological imbalance within the physiological processes amongst the minerals of tooth and oral microbial biofilms gives rise to dental caries.